2018
DOI: 10.1371/journal.pone.0204908
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of human and avian influenza viruses by potassium oleate of natural soap component through exothermic interaction

Abstract: An influenza epidemic is still a problem despite the development of vaccines and anti-influenza drugs. Preventive measures such as handwashing are fundamental and important for counteracting influenza virus infection. In this study, we clarified the anti-influenza virus effects of surfactants, which are the main components of hand soaps for hand washing: potassium oleate (C18:1), sodium laureth sulfate (LES) and sodium lauryl sulfate (SDS). For a human influenza virus strain (H3N2), C18:1 reduced the infectivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 11 publications
1
26
0
1
Order By: Relevance
“…One interesting example of a mechanistic study is of the inactivation of human (H3N2) and avian (H5N3) influenza viruses by potassium oleate (C18:1), sodium laureth sulfate (LES) and sodium lauryl sulfate (SLS) using isothermal titration (ITC). 159 It found that surfactant-virus interaction was exothermic for LES but endothermic for the other two, with LES being the least effective inactivation agent, and C18:1 being the most effective. The authors speculated on molecular mechanisms, suggesting, for example, that there was strong electrostatic interaction between the negative head group of C18:1 and the positively-charged hemagglutinin proteins embedded in the viral lipid envelope.…”
Section: Sanitisingmentioning
confidence: 99%
“…One interesting example of a mechanistic study is of the inactivation of human (H3N2) and avian (H5N3) influenza viruses by potassium oleate (C18:1), sodium laureth sulfate (LES) and sodium lauryl sulfate (SLS) using isothermal titration (ITC). 159 It found that surfactant-virus interaction was exothermic for LES but endothermic for the other two, with LES being the least effective inactivation agent, and C18:1 being the most effective. The authors speculated on molecular mechanisms, suggesting, for example, that there was strong electrostatic interaction between the negative head group of C18:1 and the positively-charged hemagglutinin proteins embedded in the viral lipid envelope.…”
Section: Sanitisingmentioning
confidence: 99%
“…Detergents can be used to inactivate lipid enveloped viruses such as coronaviruses by disrupting the viral envelope, therefore rendering them unable to attach or enter cells (26)(27)(28)(29).…”
Section: Sars-cov-2 Inactivation By Detergentsmentioning
confidence: 99%
“…Detergents can be used to inactivate lipid enveloped viruses such as coronaviruses by disrupting the viral envelope, therefore rendering them unable to attach or enter cells (24)(25)(26)(27).…”
Section: Sars-cov-2 Inactivation By Detergentsmentioning
confidence: 99%